Innovative Empowerment Strategies: Building a Creative Environment for Young Professionals in the Small Business Sector - Rahindra, Hendy Arsyad; Wisnujati, Nugrahini Susantinah (ADMAN: Journal of Contemporary Administration and Management, 2024)
Small businesses play a crucial role in the economy, particularly in creating jobs, diversifying the economy, and supporting local economic growth. However, young professionals engaged in small businesses often face challenges in reaching their full potential due to various factors. This research aims to develop innovative empowerment strategies that can assist young professionals in the small business sector in overcoming challenges and enhancing their abilities to generate and implement innovative ideas. The research method employed is a literature review with a qualitative approach and descriptive analysis. Descriptive analysis is utilized to outline and interpret findings from articles obtained from Google Scholar within the timeframe of 2001-2023. The study results indicate that innovative empowerment plays a key role in developing young professionals in the small business sector. Through descriptive analysis, various strategies have been identified to help build a creative environment for young professionals. From continuous education and training to collaboration with external parties, each step plays a crucial role in fostering a strong and sustainable culture of innovation. By implementing these strategies, organizations can ensure they remain relevant and competitive amidst continuous changes in the business world.